A survey of color image watermarking: State-of-the-art and research directions. (July 2021) - Mahto, Dhiran Kumar; Singh, A.K.
Highlights: A comprehensive and up-to-date review of watermarking algorithms for color images is presented. A detail overview of watermarking along with current applications and performance measures are discussed. Comparative analysis of the reviewed algorithms and their limitations are discussed to guide future directions. Abstract: Color image watermarking has achieved great success in various applications such as copy protection, content authentication, tamper detection and recovery, etc. The present paper provides a detailed overview of watermarking along with its characteristics, evaluation metrics, and current applications. We then provide a comprehensive survey of different approaches along with their merits and limitations. Furthermore, we summarize each of the approaches in detail, including objectives, goals, embedding location, evaluation metrics, and weaknesses, and discuss recent challenges and their possible solutions. We believe this paper will provide readers with comprehensive insight into the field of watermarking research. Graphical abstract: Image, graphical abstract